CORPORATE BUSINESSES STRATEGY OF SINGLE CUSTOMER - Ishak, Riza; Ardhiadi, Rizky (Jurnal Riset Bisnis dan Manajemen, 2024)
Model company relationship management most important,to improve the production system related to planning and delivery, online production information system, for internal and customers increase the number of sales from the previous year. Increase production capacity, quality of production machinery, and capital for financial rating. The conclusion that the strategy carried out is with the worst scenario, because it does not guarantee that a business will be sustainable, because even though single consumer. The novelty in article, most of approach riset strategy company have face more customer, whereas this article contains a study that is to a single customer with the characteristics of a Government Company, so Porter's theory of competitive strategy does not become relevant to this type of Kwh Meter business, whereas many companies are modeled as supplying to a single customer.